Carbon Stock Estimation in Tanjung Plants (Mimusops elengi L.) in the Campus Forest of Surabaya State University - Rohmah, Daniyah Fathinur; Rachmadiarti, Fida; Fitrihidajati, Herlina; Andriani, Betty (Jurnal Biologi Tropis, 2026)
Forests have a role in the global carbon cycle by absorbing and storing carbon in the environment. One of the plants in the campus forest of Surabaya State University that can absorb carbon and store it in the form of biomass is the tanjung plant (Mimusops elengi L.). This study aims to estimate the carbon stock stored in tanjung plants (Mimusops elengi L.) in the campus forest of Surabaya State University which was carried out from September to December 2024. The research method uses a non-destructive method. The parameters measured in this study include stem diameter, circumference, height, chlorophyll content, leaf surface area and environmental parameters that support the growth of Mimusops elengi. The data collection technique was carried out by purposive sampling, at three stations with a total of 50 individuals. Statistical analysis of the data used the Pearson correlation test. Mimusops elengi was able to absorb carbon respectively by 106.03 kg; 43.96 kg and 31.89 kg. Having a biomass respectively, namely 225.08 kg/tree; 91.01 kg/tree and 67.87 kg/tree. The absorption values were 389.14 tons C/ha; 161.34 tons C/ha and 117.0 tons C/ha, respectively. The results of statistical tests on height, circumference and diameter had a positive correlation with carbon stock. Meanwhile, chlorophyll content and leaf surface area were negatively correlated with carbon stock. These results indicate that tanjung plants have significant potential in absorbing carbon in the campus forest of Surabaya State University, thus playing a role in reducing greenhouse gas emissions in the atmosphere.